The Politics of Religious Space and Mosque Based Political Engagement in Indonesia - Fikri Disyacitta; Nasiwan; Ach. Fawaidi (POLTRANS: Journal of Politics and Social Transformation, 2025)
This article examines mosques as contested spaces of political meaning through Henri Lefebvre’s theory of the production of space. Challenging the conventional view of mosques as sacred and politically neutral spaces, it argues that even claims of neutrality are politically constructed through the classification and regulation of religious activities by state and non-state actors. The study addresses a gap in existing research, which has largely focused on electoral mobilisation, radicalism, and formal relations between religious institutions and the state, by examining the everyday processes through which mosque spaces acquire and negotiate political meanings. Using a qualitative approach, the study analyses three Indonesian mosques representing distinct religious communities: Pathok Negoro Mosque, associated with traditionalist Islam Husainiyah Jakarta, representing the Shia community and An-Nur Mosque, representing the Ahmadiyya community. Data were collected through in-depth interviews, direct observation, and secondary sources between October and November 2016. The findings demonstrate that mosques are actively produced through spatial practices, everyday religious routines, collective experiences, and interactions between internal and external actors, generating competing meanings as sacred, social, cultural, and political spaces. The study concludes that the politics of the mosque lies not only in explicit political mobilisation but also in ongoing struggles over representation, identity, recognition, belonging, and power.